Interdecadal Pacific Oscillation Drives Enhanced Greenland Surface Temperature Variability During the Last Glacial Maximum - Song, Zhaoyang; Latif, Mojib; Park, Wonsun; Zhang, Yuming; Song, Zhaoyang; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Latif, Mojib; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Park, Wonsun; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany (Geophysical Research Letters, 2020)
Stable oxygen isotope records from central Greenland suggest disproportionally large long‐term surface air temperature (SAT) variability during the Last Glacial Maximum (LGM) relative to preindustrial times. Large perturbations in mean atmospheric circulation and its variability forced by extensive Northern Hemisphere ice sheet coverage have been suggested as cause for the enhanced Greenland SAT variability. Here, we assess the factors driving Greenland SAT variability during the LGM by means of dedicated climate model simulations and find remote forcing from the Pacific of critical importance. Atmospheric teleconnections from the Interdecadal Pacific Oscillation (IPO), a multidecadal oscillation of sea surface temperature in the Pacific Ocean, strongly intensify under LGM conditions, driving enhanced surface wind variability over Greenland, which in turn amplifies SAT variability by anomalous atmospheric heat transport. A major role of the IPO in forcing Greenland SAT variability also is supported by a number of models from the Paleoclimate Modeling Intercomparison Project Phase III. Plain Language Summary: Stable oxygen isotope records, a proxy for the local surface air temperature (SAT), from central Greenland indicate disproportionally large reductions in the multidecadal variability from the Last Ice Age (Last Glacial Maximum, LGM; about 21,000 years before present) to modern times. A climate model simulates the changes in multidecadal Greenland SAT variability as inferred from the proxy data. The enhanced variability during the LGM is largely remotely driven by the Interdecadal Pacific Oscillation (IPO), a multidecadal oscillation of sea surface temperature (SST) in the Pacific Ocean. Atmospheric teleconnections from the IPO strongly intensify under glacial conditions, driving enhanced surface wind variability over Greenland and through atmospheric heat transport the SAT variability. Key Points: Oxygen isotope records and climate modeling show large reductions in Greenland surface temperature ...